Allergic reactions to cow’s milk proteins in medications in childhood - Santoro, Angelica; Andreozzi, Laura; Ricci, Giampaolo; Mastrorilli, Carla; Caffarelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
Cow’s milk is a frequent trigger of allergic reactions in childhood. Cow’s milk proteins can be present in pharmaceutical excipients. Methods: We have analyzed paediatric literature on allergic reactions to cow’s milk proteins in medication, focusing on the different routes of administration (inhaled, parental and oral). Results: Dry-powder inhalers may contain lactose as excipient. Lactose can be rarely contaminated with milk proteins and it may induce allergic reactions in patients with cow’s milk allergy. Case reports have described immediate hypersensitivity reactions to methylprednisolone sodium succinate 40 mg injection, a formulation that contains lactose as excipient. Some cases of anaphylaxis after receiving diphteria-tetanus-pertussis vaccine injection in children allergic to milk have been reported. Cow’s milk proteins can be detected also in oral polio vaccine, certain probiotics and lactulose syrup. Conclusions: We suggest caution in administration of pharmaceuticals containing milk allergens in children allergic to milk.